Characterization and Drug Release Evaluation of Chlorhexidine-Encapsulated Silica Nanoparticles for Potential Root Canal Disinfection - Rakhmawati, Widya; Harmaji, Andrie; Djati, Fanni Kusuma; Sunendar, Bambang (Makara Journal of Science, 2025)
The failure of root canal treatments is often attributed to bacterial invasion of the dentinal tubules, where pathogens can persist and complicate healing. Chlorhexidine digluconate, a potent antimicrobial agent, has been widely utilized for its broad-spectrum antibacterial effects. However, challenges remain in achieving efficient distribution and sustained release within the root canal system. This study investigates the encapsulation of chlorhexidine digluconate within silica nanoparticles as a novel drug delivery system that is aimed at improving root canal treatment outcomes. Silica nanoparticles were synthesized using the sol-gel method and subsequently immersed in a 2% chlorhexidine digluconate solution for 15 to 30 minutes to achieve encapsulation. The resulting materials were characterized by scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, and ultraviolet–visible (UV–Vis) spectroscopy. SEM analysis revealed particle sizes in the range of 80–150 nm for nanoparticles aged for 15 minutes and in the range of 250–350 nm for those aged for 30 minutes. FTIR spectroscopy confirmed the presence of functional groups characteristic of silica, chitosan, and sodium alginate, indicating successful encapsulation. The UV–Vis spectrophotometry demonstrated that silica nanoparticles aged for 30 minutes exhibited a more stable and controlled release of chlorhexidine digluconate (0.08 ppm) over a 60-minute period. This study presents a novel approach for enhancing root canal treatment, in which silica nanoparticles are utilized for controlled drug delivery. Additionally, the study shows that longer aging times may offer improved stability and efficacy in sustained antimicrobial action. The findings suggest that the use of silica-encapsulated chlorhexidine nanoparticles is a promising strategy for more effective endodontic treatment because it addresses bacterial invasion and supports long-term therapeutic effects.